A Comparison of Modern and Preindustrial Levels of Mercury in the Teeth of Beluga in the Mackenzie Delta, Northwest Territories, and Walrus at Igloolik, Nunavut, Canada - Outridge, P.M.; Hobson, K.A.; McNeely, R.; Dyke, A. (ARCTIC, 2002)
Mercury (Hg) concentrations were compared in modern and preindustrial teeth of belugas (Delphinapterus leucas) and walrus (Odobenus rosmarus rosmarus) at sites in the Canadian Arctic so that the relative amounts of natural and anthropogenic Hg in modern animals could be estimated. Mercury levels in the teeth of Beaufort Sea belugas captured in the Mackenzie Delta, Northwest Territories, in 1993 were significantly (p = 0.0001) higher than those in archeological samples dated A.D. 1450-1650. In terms of geometric means, the Hg levels in modern animals were approximately four times as high as preindustrial levels in 10-year-old belugas, rising with age to 17 times as high in 30-year-olds. Because Hg levels in modern teeth were highly correlated with those in soft tissues, including muscle and muktuk, which are part of traditional human diets, it is likely that soft-tissue Hg has increased to a similar degree over the past few centuries. The increase was not due to dietary differences over time, as shown by analysis of stable-C and -N isotopes in the teeth, and was unlikely to be due to sex differences or to chemical diagenesis of historical samples. Industrially related Hg inputs to the Arctic Ocean and Canadian Arctic Archipelago may be the most likely explanation for the increase. If so, then 80-95% of the total Hg in modern Beaufort Sea belugas more than 10 years old may be attributed to anthropogenic activities. In contrast, tooth Hg concentrations in walrus at Igloolik, Nunavut, were no higher in the 1980s and 1990s than in the period A.D. 1200-1500, indicating an absence of industrial Hg in the species at this location. On a comparé les concentrations de mercure (Hg) dans des dents de bélugas (Delphinapterus leucas) et de morses (Odobenus rosmarus rosmarus) de notre époque et de l'ère préindustrielle, à des lieux situés dans l'Arctique canadien de façon à estimer les montants relatifs de Hg naturel et anthropique chez les individus contemporains. Les niveaux de mercure dans les dents de bélugas de la mer de ...